Year‐round records of sea salt, gaseous, and particulate inorganic bromine in the atmospheric boundary layer at coastal (Dumont d'Urville) and central (Concordia) East Antarctic sites. Issue 2 (23rd January 2016) - Legrand, Michel; Yang, Xin; Preunkert, Susanne; Theys, Nicolas
Abstract: Multiple year‐round records of bulk and size‐segregated compositions of aerosol were obtained at the coastal Dumont d'Urville (DDU) and inland Concordia sites located in East Antarctica. They document the sea‐salt aerosol load and composition including, for the first time in Antarctica, the bromide depletion of sea‐salt aerosol relative to sodium with respect to seawater. In parallel, measurements of bromide trapped in mist chambers and denuder tubes were done to investigate the concentrations of gaseous inorganic bromine species. These data are compared to simulations done with an off‐line chemistry transport model, coupled with a full tropospheric bromine chemistry scheme and a process‐based sea‐salt production module that includes both sea‐ice‐sourced and open‐ocean‐sourced aerosol emissions. Observed and simulated sea‐salt concentrations sometime differ by up to a factor of 2 to 3, particularly at DDU possibly due to local wind pattern. In spite of these discrepancies, both at coastal and inland Antarctica, the dominance of sea‐ice‐related processes with respect to open ocean emissions for the sea‐salt aerosol load in winter is confirmed. For summer, observations and simulations point out sea salt as the main source of gaseous inorganic bromine species. Investigations of bromide in snow pit samples do not support the importance of snowpack bromine emissions over the Antarctic Plateau. To evaluate the overall importance of the bromine chemistry over East Antarctica, BrO simulations were also discussed with respect data derived from GOME‐2 satellite observations over Antarctica. Key Points: Strong bromide depletion relative to sodium in Antarctic sea‐salt aerosol No significant bromine snow emission over Antarctica Significant sea‐salt contributions from sea ice and open ocean sources